Implementation of Imam Al-Shaṭibi’s Maqaṣid al-Shariah in the Development of Intellectual Property Rights Waqf Policies - Syaiful Anam (Et-Tijarie, 2025)
This study aims to elaborate the implementation of Imam al-Shaṭibi’s maqaṣid al-shariah in formulating policies related to the waqf of Intellectual Property Rights (IPR). Although Law Number 41 of 2004 on Waqf recognizes IPR as a legitimate waqf object, no technical regulations have been established to ensure its implementation. As a result, the potential of IPR waqf has not been optimally realized as an instrument for empowering the Muslim community. This research employs a qualitative normative method through a comprehensive literature review. The findings reveal that IPR waqf policies must be grounded in the principles of ḥifẓ al-māl, ḥifẓ al-ʿaql, and ḥifẓ al-dīn in order to ensure sustainability of benefits, legal certainty, and long-term public welfare. Thus, al-Shaṭibi’s maqaṣid al-shariah serves as a pivotal paradigm in designing IPR-based waqf policies within the contemporary legal framework.Keywords: Maqāṣid al-sharīʿah, al-Shāṭibī, intellectual property rights, policy development